DETERMINATION OF SAND MINING PROSPECTIVE ZONES BASED ON SEDIMENT THICKNESS ANALYSIS USING HVSR MICROTREMOR AND GRAVITY METHODS: A CASE STUDY IN CANGKRINGAN, SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Sidik, Firdos Bahar; Ramadeo, Muhammad Gilang; Wulandari, Maria Diyah Ayu; Khumairo, Savira Zahrul; Nurkholijah, Ekasari; Pangestu, Farizki Budi; Fitrinova, ⁠Safina; Muhlisin, Haris (Ikatan Dosen Menulis, 2024)
Mount Merapi is the most active type A volcano, especially on the island of Java. It produces sediment products totaling 140 million m3 located at the peak of Mount Merapi, descending through the mountain slopes to rivers originating from Mount Merapi. This sediment is subsequently utilized as a sand mining area. Therefore, it is necessary to determine prospect zones for sand mining that align with environmental, economic, and mitigation aspects in the Cangkringan area, Sleman, Yogyakarta Special Region. Seventeen microtremor measurement points were used with the Horizontal to Vertical Spectral Ratio (HVSR) method to determine sediment thickness, constituent lithology, and mining zones suitable for safety and mitigation aspects. Additionally, the gravity method was employed with 247 measurement stations obtained from GGM Plus to determine rock density and estimated thickness based on 2.5D modeling. The study resulted in the distribution of dominant soil frequencies ranging from 0.5 Hz to 7.5 Hz. High frequencies indicate old rocks, while medium frequencies suggest alluvial rocks with a thickness of ± 5 m. Low frequencies indicate alluvial rocks with a thickness exceeding ± 30 meters. Based on gravity results, the average depth is ±90-200 m with a density of 2.6 g/cm3, reflecting the depth of the bedrock in the study area, composed of andesitic volcanic rock. Soil vulnerability analysis in the study area classified into three categories, with values of 4.2-5.4 being highly vulnerable to surface deformation, values of 1.8-3.8 indicating moderate vulnerability, and values of -0.2-1.4 representing low vulnerability. Furthermore, the Peak Ground Acceleration (PGA) ranges from 500-1200 gal with intensity X. Ground Shaking Spectrum (GSS) data indicates that the study area experiences vibration phenomena with elastic soil dynamics. Therefore, the exploitation of sand resources in the Cangkringan area can be conducted in the southern region of Mount Merapi, approximately 2 km away from the mountain center. This is because the southern part of the research area has suitable mitigation measures. Moreover, based on the analysis, sediment thickness in this area ranges from ± 5-30 meters.